2011
DOI: 10.1016/j.rbmo.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene polymorphisms in North Indian patients with recurrent miscarriages

Abstract: The association of four common polymorphisms of vascular endothelial growth factors (VEGF) with recurrent miscarriages(RM) was evaluated in North Indian women for 200 patients with RM and 200 controls. The subjects were genotyped for the polymorphisms 2578C/A, 2549 18-bp I/D, 1154G/A and +936C/T. Association of VEGF genotypes, alleles and haplotypes with recurrent miscarriage were evaluated by Fisher’s exact test. 1154G/A and +936C/T modified the risk of RM. The 1154A allel and +936T allel significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 19 publications
3
34
1
Order By: Relevance
“…The lack of the association with RSA and +936C/T (rs3025039, 3´UTR region) in the current study was also reported in Bahraini (Brazilian, 27), Greek (28) and Korean (29) population studies while Aggarwal et al (19) studied North Indians and it was in disagreement with previous studies and our fi ndings. In the present study, we did not report +936 T allele frequency of both case and controls.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The lack of the association with RSA and +936C/T (rs3025039, 3´UTR region) in the current study was also reported in Bahraini (Brazilian, 27), Greek (28) and Korean (29) population studies while Aggarwal et al (19) studied North Indians and it was in disagreement with previous studies and our fi ndings. In the present study, we did not report +936 T allele frequency of both case and controls.…”
Section: Discussioncontrasting
confidence: 95%
“…In the present study, we did not report +936 T allele frequency of both case and controls. Homozygosity for this allele is also rare (0.8-4 %) in different populations (19,28). The +936C/T SNP is located in 3´UTR region and was linked to altered VEGF expression in different studies (12, 30, 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that constructs containing the 18-bp deletion had a 1.95-fold increase in the transcriptional activity compared with those containing the insert (Yang et al, 2003). Contrary to previous reports of ID or DD genotypes being associated with systemic sclerosis in the European Caucasians (Allanore et al, 2007), HCC in the Chinese Han population (He et al, 2010), and in recurrent miscarriages in the North Indian population (Aggarwal et al, 2011), in the present study, frequencies of the II genotype and I allele were significantly higher in breast cancer patients than controls thus indicating a probable decreased transcriptional activity of VEGF in patients.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have analyzed the -2549 I/D polymorphism in the context of susceptibility to various diseases like Behcet's disease (BD) (Salvarani et al, 2004), asthma (Lachheb et al, 2008), HCC (He et al, 2010), recurrent miscarriages (Aggarwal et al, 2011), and end-stage renal disease (Prakash et al, 2012). Association of the DD genotype of the -2549 I/D polymorphism has been reported with diabetic retinopathy (Awata et al, 2002;Buraczynska et al, 2007), diabetic nephropathy (Yang et al, 2003), peripheral artery disease (Bleda et al, 2012), and end-stage renal disease (Prakash et al, 2012).…”
mentioning
confidence: 99%